Analisis dan Desain Pembelajaran Merdeka Belajar pada Mata Pelajaran PAI - Kuni Baridah Aini; Moh. Sutomo; Mashudi Mashudi (Fakta: Jurnal Pendidikan Agama Islam, 2022)
Education is the process of facilitating learning, or the acquisition of knowledge, skills, values, morals, beliefs, and habits. Through education, one can have an understanding of something that makes him a critical human being in thinking and acting. The measure of educational success is seen from the involvement and participation of teachers as educators, students as learners, learning materials provided, teaching methods and infrast ructure provided. The new Minister of Education and Culture of Indonesia, Nadiem Makarim, has since issued circular letter number 1 of 2020 regarding the policy of independent learning in determining student graduation, raising pros and cons from various groups, "Freedom of Learning" or "Freedom of Learning". The concept of "Freedom of Learning", which frees educational institutions and encourages students to innovate and encourage creative thinking. This concept was then accepted considering the vision and mission of Indonesian Education in the future for the sake of creating quality human beings who are able to compete in various fields of life. This study aims to examine and analyze the formulation of independent learning policy formulations in the implementation of learning through SWOT analysis. The research method used is a literature review approach with descriptive qualitative methods. The results of the study show that threats and weaknesses still dominate the existing strengths and opportunities, the availability of human resources, information technology facilities and support from the competent government is still in conflict with the reality on the ground in the community who still stutters in mastering technology and budget constraints in managing and supporting the successful implementation of the independent learning policy. . With this article that examines the policy of independent learning, it is hoped that there will be further research that directly observes in the field to obtain a more concrete picture to provide alternative solutions in improving government policies.